Surface water distribution challenges and elephant impacts on woody species in Mana Pools National Park, Zimbabwe - Matsa, Mark; Shuche, Courage; Musasa, Tatenda; Defe, Rameck (Tropical Ecology, 2022)
This study assessed the relationship between surface water distribution and elephant impacts on the Zambezi River flood plain, Mana Pools National Park woody species ecosystem. Water availability and forage are major requirements for African elephant distribution within an ecosystem landscape in Zimbabwe. Surface water unavailability reduce elephant home range to around peripheries of water bodies and this is intensifying the destruction of wood species around these water bodies. The study adopted a mixed methods research design which combined qualitative and quantitative methods. Field data were collected between 10 January 2017 and 14 February 2019. Questionnaires, interviews and field observations were the major tools used to collect data in Mana Pools National Park. Data were analysed using the Statistical Package for Social Sciences version 20.0. Inferential statistics were employed to determine the relationship between elephant activity and damage of woody species. Chi square test results revealed that there is a significant relationship (P < 0.05; P = 0.001) between elephant activity and woody species damage. This means that woody species damage in the Mana Pools National Park Zambezi Valley flood plain can be attributed to elephant activity. This study recommends that Government and Zimbabwe Parks and Wildlife Management Authority (ZPWMA) should formulate effective elephant population analysis through periodic surveys in order to continuously update the national data base of elephant population trends in areas such as Mana Pools National Park.